Effectiveness of collaborative learning method in mastering the skill performance of students of the Institute of Fine Arts For boys in Arabic calligraphy (Journal of the College of Basic Education, 2020)
The teacher of Arabic calligraphy must select a suitable technical technique to teach Arabic calligraphy to achieve its educational goal without neglecting the aesthetic and technical aspects required. The researcher showed through the exploratory study that there is a weakness in the capabilities of students to perform the skills of Arabic calligraphy in the light of a clear plan and technology, which encouraged him to think about the necessity of adopting scientific mechanisms to teach Arabic calligraphy through employing the method of cooperative learning, and the research structure contained four Chapters, the first chapter of it included the methodological framework and included the problem of research, its importance, purpose and limitations and the definition of terms, while the second chapter was devoted to the theoretical framework that included two topics the first was devoted to cooperative learning and the second talked about Arabic calligraphy. As for the third chapter, it deals with the research methodology and procedures, while the fourth and final chapter is devoted to the results and conclusions, the most important of which are:Cooperative education is one of the good teaching methods that has been proven to be used in developing students ’skills in performing Arabic calligraphy skills.There are misconceptions held by a number of members of the experimental group about how to perform Arabic calligraphy skills and implement its requirements, and for this reason the effect of typical teaching plans on developing their skills in Arabic calligraphy has appeared.